Chemical immobilisation and satellite tagging of free‐living southern cassowaries. Issue 7 (July 2014) - Campbell, HA; Dwyer, RG; Sullivan, S; Mead, D; Lauridsen, G
<x xml:space="preserve">Abstract</x> Background The southern cassowary (Casuarius casuarius johnsonii) attains 1.8 m in height and over 80 kg in weight. These large birds are equipped with large claws and, although not a direct threat to humans, they have caused serious injury to handlers and members of the public. Methods and results This study describes chemical immobilisation, restraint, transport and post‐monitoring (satellite tracking) methodologies for adult and juvenile southern cassowaries, captured and released from their natural environment. Conclusions The described methods have improved the management and research opportunities for the southern cassowary and may be transferable to other species of large ratite.